2022
DOI: 10.1111/acps.13462
|View full text |Cite
|
Sign up to set email alerts
|

Metformin for the prevention of clozapine‐induced weight gain: A retrospective naturalistic cohort study

Abstract: Objective: Clozapine is presently the sole antipsychotic with an indication for treatment-resistant Schizophrenia, but is associated with significant weight gain and other metabolic aberrations. This retrospective chart review aimed to evaluate the effectiveness of adjunctive metformin in preventing clozapineinduced weight gain. Methods: We conducted a retrospective chart review of patients newly initiated on clozapine at the Centre for Addiction and Mental Health in Canada, from November 2014 to April 2021. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Aufgrund fehlender Grenzwerte soll eine Ernährungsberatung und die Aufforderung zu ausreichender Bewegung durchgeführt werden, auch eine adjuvante Therapie mit z. B. Metformin kann erwogen und gegebenenfalls im Sinne der Prophylaxe auch zeitgleich eingesetzt werden [ 21 , 22 ].…”
Section: Resultateunclassified
“…Aufgrund fehlender Grenzwerte soll eine Ernährungsberatung und die Aufforderung zu ausreichender Bewegung durchgeführt werden, auch eine adjuvante Therapie mit z. B. Metformin kann erwogen und gegebenenfalls im Sinne der Prophylaxe auch zeitgleich eingesetzt werden [ 21 , 22 ].…”
Section: Resultateunclassified
“…Few studies have examined the role of metformin in the prevention of AiWG. A recent retrospective cohort study included in this current issue showed that metformin was associated with less weight gain compared to the control group after 6 (−0.15 kg vs. 2.99 kg) and 12 months (−0.67 kg vs. 4.72 kg) in 396 participants newly initiated on clozapine, of which 69 were on metformin ≤3 months after clozapine initiation 37 . Adverse events of metformin are mainly gastro‐intestinal.…”
mentioning
confidence: 90%
“…A recent retrospective cohort study included in this current issue showed that metformin was associated with less weight gain compared to the control group after 6 (À0.15 kg vs. 2.99 kg) and 12 months (À0.67 kg vs. 4.72 kg) in 396 participants newly initiated on clozapine, of which 69 were on metformin ≤3 months after clozapine initiation. 37 Adverse events of metformin are mainly gastro-intestinal. A placebo-controlled study randomized 25 participants with schizophrenia, schizoaffective, bipolar or depressive disorder to olanzapine and metformin 2000 mg/day or olanzapine and placebo for 24 weeks.…”
mentioning
confidence: 99%
“…The increase is usually more than 7% of the patient's body weight [230]. Fortunately, this adverse effect can be countered with an adequate diet and regular physical activity or, as a second option, the administration of controlled-release metformin may be considered [231]. Noteworthily, while most patients who experienced hyperglycaemia with Clozapine had risk factors for diabetes, hyperglycaemia was also reported in patients without risk factors.…”
Section: Metabolic Side Effectsmentioning
confidence: 99%